ANALISIS KETERAMPILAN PROSES SAINS SISWA MENGGUNAKAN MODEL PEMBELAJARAN REACT (REALATING, EXPERIENCING, APPLYING,COOPERATING, TRANSFERING) PADA MATERI ASAM BASA - Budi Saputra; Zona Octaria (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This research aimed at knowing the quality of student science process Skill Using REACT (Relating, Experiencing, Applying, Cooperating, Transfering) on Acid-Base Indicator subject of Acid-Base lesson. The Samples were the tenth-grade students of TLM Class at Vocaltional High School of Abdurrab Pekanbaru, and they were 19 students selected by using Purposive sampling tecnique. Observation sheer and posttest quetion that was in the form of essey were used to measure student science process skill. Mixed method was used in this research with The One-Shot Case Study design. Based on the date obtained, the quality of student science process skill using REACT (Relating, Experiencing, Applying, Cooperating, Transfering) overall was on good category. The highest aspect of science process skill was implementing the concept with 76,9 % mean percentage, and the lowest aspect was communicating with 66,7 % mean percentage.